A Formula for n-times Integrated Semigroups (nN) - Vugdalić, Ramiz (Sarajevo Journal of Mathematics, 2024)
Motivated with Hille's first exponential formula for C_0 semigroups, we prove a formula for n-times integrated semigroups. At first we prove a formula for twice integrated semigroup, and, later, we generalize this formula for n-times integrated semigroups. 2000 Mathematics Subject Classification. 47D60, 47D62